Sistema para las tutorías académicas en las universidades ecuatorianas. Caso Universidad Estatal de Milagro - Correa Peralta, Mirella Azucena (2017)
The development of this research starts from the need to include university teachers in academic tutoring activities, an activity that is stipulated by the Regulation of Teaching Staff in Ecuador. The objective is to identify the incidence of academic tutoring processes in universities for to be systematized. This study was carried out at the State University of Miracle in 2014, applying a survey to 1256 students, 126 teachers and 28 managers, analyzing: 1. Processes, 2. Standardization and 3. Application of academic tutorials. 97% of the students agree that there must be academic accompaniment with specialized teachers (70%) and fluent communication (90%). As a product, a process diagram and a UML diagram are presented, concluding that the technology contributes in the assignment of schedules, monitoring and communication of academic and virtual tutorials.